Modelling the Efficacy of Febrile Heating in Infected Endotherms - Lewis, Gregory; Bonsall, Michael B. (Frontiers in Ecology and Evolution, 2021)
Fever is a response to infection characterised by an increase in body temperature. The adaptive value of this body temperature increase for endotherms is unclear, given the relatively small absolute temperature increases associated with endotherm fever, its substantial metabolic costs, and the plausibility for pathogens to adapt to higher temperatures. We consider three thermal mechanisms for fever's antimicrobial effect: 1) direct growth inhibition by elevating temperature above the pathogens optimal growth temperature; 2) further differentiating the host body from the wider environment; and 3) through increasing thermal instability of the pathogen environment. We assess these by modelling their effects pathogen on temperature dependent growth, finding thermal effects can vary from highly to minimally effective depending on pathogen species. We also find, depending on the specification of a simple physical model, intermittent heating can inhibit pathogen growth more effectively than continuous heating with an energy constraint.